Human leukocyte Antigen-B*27 allele subtype prevalence and disease association of ankylosing spondylitis among south indian population - Vikram Haridas; Praveenkumar Shetty; M Nirmal Kumar; K C Vasanthakumar; Kiran Haridas; Vitthal Khode; Anil Bargale (Indian Journal of Rheumatology)
Aim: Ankylosing spondylitis (AS) is a chronic inflammatory arthritis mainly affecting articular and extraarticular structures. AS clinical manifestations also involve sacroiliac joints and spine. Genetic factors play a key role in AS susceptibility. AS-associated subtypes of human leukocyte antigen (HLA)-B27 and other HLA-B alleles vary in different ethnic populations. There are no reports of HLA B genotype association to South Indian AS patients. In the current study, we have analyzed the HLA-B genotype association with 105 AS patients and 100 respective controls, we have also verified whether any specific clinical manifestation of AS has any pattern of HLA-B subtype association. Methods: The patients with AS were diagnosed fulfilling ASAS criteria. Before enrolling the patients, the written informed consent was obtained. The peripheral blood DNA genotyping of HLA-B27 was performed in Applied Biotechnologies 3130/3500 sequencer using SeCore HLA B Class I typing high-resolution kit from Invitrogen. Results: HLA B27 allele frequency in AS patients (74%) is significantly higher than healthy controls (3%). Most of the earlier studies associated AS with HLA B27 antigen. The current data illustrate that only 21% of AS patients presented HLA B27 antigen. HLA B27:05 and HLA B27:04 are the predominant subtypes. Early-onset of AS manifestations is seen in HLA B27 phenotypes than non-HLA B27 phenotypes. HLA B27 associated AS patients presented more severe axial manifestations such as bilateral sacroiliitis, erosions, and extra-articular features such as uveitis than non-HLA types. Positivity for HLA B27 allele predicts more severe disease course in South Indian patients with AS, similar to that in other populations. Conclusion: The current study indicates that a majority of South Indian AS patients are associated with HLA-B*27 alleles. In addtion we found that HLA-B*27 associated AS patients presented with more severe axial manifestations.